Driving Service Innovation to Increase Economic Peformance of PT Reksa Multi Usaha : The Impact of Innovative Work Behavior on Performance Among Train Attendants - Chaerudin, Ikhsan (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the influence of innovative work behavior (IWB) on service innovation performance (SIP) within the transportation service sector. Conducted at PT Reska Multi Usaha (RMU), a subsidiary of PT Kereta Api Indonesia, the research focuses on the Yogyakarta branch, engaging 58 train attendants as respondents. Primary data were collected using an online questionnaire and analyzed through the Covariance-Based Structural Equation Model (CB-SEM) using LISREL 8.80. The study identifies that IWB—comprising idea generation, idea promotion, and idea realization—positively and significantly affects SIP. High coefficients for each IWB dimension underscore the pivotal role of employees' innovative actions in enhancing service quality and fostering service innovation. The findings emphasize the critical importance of empowering frontline employees, such as train attendants, to actively contribute to service innovation by leveraging their insights from customer interactions. This research provides valuable insights for organizations seeking competitiveness in Indonesia's rapidly growing transportation sector. It highlights the necessity of fostering an innovative culture to support continuous service improvement and meet the evolving demands of a dynamic market.